AB0798 Prevalence, severity, and clinical correlates of pain in patients with systemic sclerosis. (23rd January 2014) - Teixeira, F.; Peixoto, D.; Costa, J.; Afonso, C.; Araujo, D.
Abstract : Background: Systemic sclerosis (SSc) is a multisystem disease characterized by immune system activation, fibrosis, and vasculopathy. Because SSc is a complex multisystem disease, pain may have multiple sources, patients with SSc report numerous painful symptoms, including skin breakdown, digital ulcers, Raynaud's phenomenon, musculoskeletal pain, and gastrointestinal symptom Objectives: To estimated prevalence, severity and associations between SSc clinical variables and pain in all patients with SSc and in limited cutaneous (lcSSc) and diffuse cutaneous (dcSSc) subsets. Methods: A total of 42 patients (36 females, 6 males) with a mean age 53.7±15.3 years, diagnosed according to American Rheumatism Association criteria for SSc completed a standardized clinical assessment and questionnaires about their physical and psychosocial health, including a pain severity numerical rating scale (NRS; range 0–10). Pain prevalence and severity were estimated with descriptive statistics. SSc clinical variables and pain were estimated with linear regression for the entire group and by SSc subtype. Results: Of the patients, 37 (88%) reported pain. Sixteen (39%) had mild pain [NRS 1–4], 11 (27%) moderate pain [NRS 5–7], and 15 [36%] severe pain [NRS 8–10]). Active ulcers, a high modified Rodnan skin thickness score, worse synovitis andgastrointestinal (GI) symptoms were associated with pain in multivariate analysis adjusting for demographic variables, depressive symptoms, and comorbid conditions. Patients with dcSSc reported higher mean ±SD pain than those with lcSSc (dcSSc 5.1±3.4 versus lcSSc 2.7±2.8. Conclusions: Pain symptoms were common in the present study of patients with SSc and were independently associated with more active ulcers, worse synovitis, skin thicknessand GI symptoms. Subsetting by extent of skin involvement was related to pain severity variables. Disclosure of Interest: None Declared